2017
DOI: 10.3762/bjnano.8.236
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the stability of DNA nanostructure templates by atomic layer deposition of Al2O3 and its application in imprinting lithography

Abstract: We present a method to increase the stability of DNA nanostructure templates through conformal coating with a nanometer-thin protective inorganic oxide layer created using atomic layer deposition (ALD). DNA nanotubes and origami triangles were coated with ca. 2 nm to ca. 20 nm of Al2O3. Nanoscale features of the DNA nanostructures were preserved after the ALD coating and the patterns are resistive to UV/O3 oxidation. The ALD-coated DNA templates were used for a direct pattern transfer to poly(L-lactic acid) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…This problem, however, may be overcome by coating the immobilized DNA origami nanostructures with a thin protective film. To this end, Kim et al employed atomic layer deposition (ALD) of thin (2–5 nm) Al 2 O 3 films and showed that such films not only perfectly reproduce the shape of DNA origami triangles and DNA nanotubes, but also protect the DNA nanostructure masters during repeated imprinting, washing with pure water, and extended UV/ozone exposure for 1 h [ 108 ]. In a similar approach, Matković et al used single-layer graphene as a protective layer on top of DNA origami nanostructures adsorbed on SiO 2 surfaces [ 109 ].…”
Section: Materials Science Applicationsmentioning
confidence: 99%
“…This problem, however, may be overcome by coating the immobilized DNA origami nanostructures with a thin protective film. To this end, Kim et al employed atomic layer deposition (ALD) of thin (2–5 nm) Al 2 O 3 films and showed that such films not only perfectly reproduce the shape of DNA origami triangles and DNA nanotubes, but also protect the DNA nanostructure masters during repeated imprinting, washing with pure water, and extended UV/ozone exposure for 1 h [ 108 ]. In a similar approach, Matković et al used single-layer graphene as a protective layer on top of DNA origami nanostructures adsorbed on SiO 2 surfaces [ 109 ].…”
Section: Materials Science Applicationsmentioning
confidence: 99%
“…Their results showed that a thin layer of Al 2 O 3 coating could significantly increase the stability of the DNA patterns in harsh oxidation environment and against mechanical damage. [32] However, because both the SiO 2 substrate and DNA nanostructures are hydrophilic and active toward ALD reaction, there is no selective film coating. Hui et al recently reported an area-selective ALD coating of oxides onto DNA nanostructures (Figure 6C).…”
Section: Dna-templated Dielectric and Semiconductor Nanostructuresmentioning
confidence: 99%
“…They found that shapes of DNA nanostructures were intact under conditions up to 200 °C for 10 min, 24 h exposure to alkaline, and 5 min exposure to UV/O 3 . Kim et al [ 41 ] also developed an approach to increase the stability of DNA nanostructures toward chemical or mechanical stresses. They deposited an Al 2 O 3 atomic layer on top of DNA templates, which acted as a protective coating against UV/O 3 oxidation.…”
Section: Fabricationmentioning
confidence: 99%